From Administrative Irregularities to Criminal Acts: Uncovering Corruption in State Procurement Systems - Adhi, Surya; Arifin, Ridwan; Sani, Tajudeen (PAMPAS: Journal of Criminal Law, 2025)
The procurement of goods and services within the public sector is a crucial function that supports the operation of government institutions and the delivery of public services. However, this process is often vulnerable to corruption, including bribery, collusion, and abuse of authority. This paper examines the criminal law aspects related to government procurement by analyzing various cases of corruption in Indonesia. Through a review of legal frameworks, including the Indonesian Criminal Code (KUHP) and Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption, this study explores how these regulations are applied in practice. Case studies highlight recurring issues such as inflated project costs, fictitious procurement, and favoritism in awarding contracts. The paper also evaluates the role of law enforcement agencies, particularly the Corruption Eradication Commission (KPK), in investigating and prosecuting procurement-related offenses. While significant progress has been made in combating corruption, challenges remain in the consistent application of the law, limited resources, and political interference. This analysis emphasizes the need for stronger preventive mechanisms, greater transparency, and capacity-building among procurement officials to reduce legal violations. By examining real-world cases and their legal outcomes, this study aims to contribute to a better understanding of the intersection between criminal law and public procurement, and to support the development of more effective anti-corruption strategies within the public sector. ABSTRAK Pengadaan barang dan jasa di sektor publik merupakan fungsi penting yang mendukung operasional lembaga pemerintahan serta pelayanan kepada masyarakat. Namun, proses ini sering kali rentan terhadap praktik korupsi, seperti suap, kolusi, dan penyalahgunaan wewenang. Artikel ini membahas aspek hukum pidana yang terkait dengan pengadaan pemerintah melalui analisis berbagai kasus tindak pidana korupsi di Indonesia. Dengan mengkaji kerangka hukum, termasuk Kitab Undang-Undang Hukum Pidana (KUHP) dan Undang-Undang Nomor 31 Tahun 1999 junto Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi, studi ini mengevaluasi penerapan hukum dalam praktik. Studi kasus menunjukkan berbagai permasalahan yang berulang, seperti penggelembungan anggaran, pengadaan fiktif, dan praktik nepotisme dalam pemberian kontrak. Artikel ini juga menyoroti peran lembaga penegak hukum, khususnya Komisi Pemberantasan Korupsi (KPK), dalam mengusut dan menindak pelanggaran terkait pengadaan. Meskipun telah ada kemajuan dalam upaya pemberantasan korupsi, masih terdapat tantangan dalam konsistensi penegakan hukum, keterbatasan sumber daya, serta intervensi politik. Analisis ini menekankan pentingnya mekanisme pencegahan yang lebih kuat, transparansi yang lebih tinggi, serta peningkatan kapasitas aparatur pengadaan untuk meminimalisir pelanggaran hukum. Dengan menelaah kasus-kasus nyata dan hasil hukumnya, studi ini bertujuan memberikan pemahaman yang lebih dalam mengenai hubungan antara hukum pidana dan pengadaan publik, serta mendukung pengembangan strategi anti-korupsi yang lebih efektif di sektor pemerintahan.